The Effect of Principal Leadership Through Organizational Citizenship Behavior of Teachers on the Quality of Islamic Religious Education Learning - Malla, Hamlan Andi Baso; Hamka, Hamka; Kurnia, Kurnia; Abu, Ardillah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This paper investigates the pivotal role of school principals in shaping and enhancing Organizational Citizenship Behavior (OCB) among teachers to enhance the quality of Islamic Religious Education (IRE) instruction. The research was conducted at SMA Negeri 1 Bumi Raya, located in Morowali Regency, Central Sulawesi Province, Indonesia, employing descriptive-qualitative methodologies. Data analysis was conducted using the N-Vivo software. The findings of this study underscore the multifaceted role of principals in fostering OCB. Principals emerge as both motivators and supervisors within the educational setting. As motivators, they offer support and encouragement to teachers facing challenges, convene regular meetings to address issues, and deliver motivating messages during ceremonial gatherings. As supervisors, they diligently assess and oversee the performance of their teaching staff, ensuring a high standard of educational delivery. Internally, factors influencing OCB include teachers' personality development and perception of organizational support. Externally, the quality of relationships between superiors and subordinates and the length of service significantly impact OCB outcomes. In summary, this research sheds light on the pivotal role of school principals as motivators and supervisors and identifies key internal and external factors that influence the optimization of OCB among teachers. Understanding these dynamics is crucial for improving the management and quality of Islamic Religious Education learning in educational institutions.